Role of galactomannan determinations in bronchoalveolar lavage fluid samples from critically ill patients with chronic obstructive pulmonary disease for the diagnosis of invasive pulmonary aspergillosis: a prospective study - He, Hangyong (BioMed Central, 2012)
INTRODUCTION: Critically ill chronic obstructive pulmonary disease (COPD) patients are at particular risk of invasive pulmonary aspergillosis (IPA). Our aims were to determine whether bronchoalveolar lavage fluid (BALF) galactomannan (GM) has a higher sensitivity and specificity than serum GM or lower respiratory tract (LRT) sample culture. Furthermore, we aimed to investigate what the optimal cut-off value would be for BALF GM. METHODS: In this prospective single-center study, BALF and serum samples were collected from critically ill COPD patients on the first day of their intensive care unit admission. RESULTS: Of 50 critically ill COPD patients admitted, BALF and serum samples were collected in 34 patients. According to the receiver operating characteristics (ROC) curve, an optical density (OD) ratio of 0.8 was chosen as the cut-off value for GM in BALF. Compared to serum GM and LRT Aspergillus isolation, BALF GM yield a better sensitivity, specificity, positive and negative predictive values of 88.9%, 100%, 100% and 94.4%, respectively. Areas under the ROC curve were 0.912 (95%CI, 0.733 to 0.985) for BALF GM, and 0.879 (95%CI, 0.691 to 0.972) for serum GM results from the first day of ICU admission. Pairwise comparison of ROC curves showed P = 0.738. The OD ratio of BALF GM in IPA patients were significantly higher than those of non-IPA patients (2.88 ± 2.09 versus 0.49 ± 0.19, P = 0.009), and the OD ratio of BALF GM was significantly higher than serum GM in IPA patients (2.88 ± 2.09 versus 0.87 ± 0.47, P = 0.023). Positive BALF GM was seen earlier than LRT secretion culture (1 day versus 3.8 days). CONCLUSIONS: Compared to serum GM and LRT Aspergillus isolation, BALF GM seems to have a better sensitivity in the diagnosis of IPA in critically ill COPD patients. The ROC curve suggests a possible cut-off value of 0.8 for GM from BALF specimens in critically ill COPD patients.